DAMPAK COVID-19 TERHADAP KONDISI SOSIAL EKONOMI PEDAGANG KAKI LIMA DI STADION MAULANA YUSUF CICERI KOTA SERANG - Ubay Haki; Mamay Komarudin (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
street vendors or better known as street vendors, is a term for sellers  of      merchandise who sell their wares in places that can be passed by pedestrians or public spaces. In carrying out their activities, street vendors are limited by the Enforcement of Community Activity Restrictions (PPKM) in Serang City, considering that Covid-19 victims continue to grow. This scientific article intends to find out: 1) The difference in capital income obtained, 2) Changes in the economic activities of street vendors at the Maulana Yusuf Ciceri Stadium, Serang. A total of 70 street vendors in Ciceri Stadium were taken as research samples. data that includes age, gender, education level, capital, income, models of interacting with potential buyers during the pandemic and before the pandemic, using structured interview techniques and observation. then the data is analyzed through quantitative descriptive method. the capital and income of street vendors at Ciceri Stadium during the pandemic period decreased compared to before the pandemic, due to the lack of enthusiasm in increasing their productivity. The relationship between street vendors and potential buyers remains intact but does not take any anticipatory efforts in overcoming the changing situation. working hours, duration of work and places to sell remain at the Ciceri stadium so it is difficult to maintain the number of buyers